ZB Financial Holdings Virtual Banking and Loan Application Systems - Mlambo, Douglas (Midlands State University, 2017)
ZB Financial Holdings Virtual Banking and Loan Application system is a system that enables customers to log into the system and be able to carry out all the transactions such as having the access to view their account balances, view all latest transactions and be able to download bank statements in portable document format. Data was gathered by the use of interviews, questionnaires and observations and this brought out the expectations of the customers and the employees as well as their grievances towards the manual system. The fact finding techniques helped the researcher to note that the customers wanted a system that can enable them to carry out transactions from their geographical locations and be able to track their requests removing the entire bore some procedures. The researcher also was able to note that the company employees wanted a system that reduces too much paperwork from the old system and saves time. Upon the completion of the system, it was deployed to the end users together with the user manuals since the customers have showed the highest levels of appreciation towards the use of the new system. The researcher gained a lot of experience that can be used in the future when researching other projects. Therefore, the he or she can be able to overcome all the hindering factors that can be faced when proposing the projects in the future up to its completion since the implementation of the Virtual banking and Loan Application System for the ZB Bank left the researcher with highest levels of project management knowledge and skills.